2019
DOI: 10.1016/j.jclepro.2019.03.226
|View full text |Cite
|
Sign up to set email alerts
|

Linking stakeholder engagement to profitability through sustainability-oriented innovation: A quantitative study of the minerals industry

Abstract: Firms' capability to develop sustainability-oriented innovation (SOI) can be enhanced by stakeholder engagement (SE) in order to acquire a wide range of external knowledge to support innovation efforts and outcomes. While we understand some of the transactional and relational attributes at stake for firms to leverage engagement with external stakeholders, we do not yet fully understand all the underlying mechanisms that are conducive to greater SOI outputs. At the same time, stakeholder theory emphasizes the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(75 citation statements)
references
References 84 publications
1
56
0
Order By: Relevance
“…CSR is also important from the employee perspective. The CSR activities of a company have a significant influence on employee engagement [81]; customer behavior in choosing products [82,83]; stakeholders, whereby sustainability-oriented innovation enables firms to reap financial benefits [84]; and company owners, given that taking advantage of CSR activities leads to an increase in profits [85]. The hashtag #CSR was most strongly linked to the hashtag #esg, i.e., environmental, social, and governance (ESG).…”
Section: Resultsmentioning
confidence: 99%
“…CSR is also important from the employee perspective. The CSR activities of a company have a significant influence on employee engagement [81]; customer behavior in choosing products [82,83]; stakeholders, whereby sustainability-oriented innovation enables firms to reap financial benefits [84]; and company owners, given that taking advantage of CSR activities leads to an increase in profits [85]. The hashtag #CSR was most strongly linked to the hashtag #esg, i.e., environmental, social, and governance (ESG).…”
Section: Resultsmentioning
confidence: 99%
“…Innovation helps to manage businesses in a sustainable way, which will have positive impacts not only on environment, but also on society by improving local communities and local businesses. According to Silvestre (2015) and Maier et al (2020), innovation is a key mechanism for addressing sustainable development; moreover, innovation can be driven by sustainability (Nidumolu et al, 2009;Ghassim and Bogers, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…That is a consequence from the fact that companies that try to develop processes, products or services that harm less the environment, for example, improve their image, reputation and legitimacy with stakeholders (Aguilera-Caracuel; Ortiz-de-Mandojana, 2013). Ghassim and Bogers (2019) investigated companies of the mining industry and proved that the Sustainability-oriented innovation (SOI) links stakeholder's engagement with profitability. They found that the company's ability to develop Sustainability-oriented innovation (SOI) is improved by the engagement of stakeholders, as it provides a wide range of knowledge that supports the efforts and results of innovations.…”
Section: Process and Organizational Innovation (Poi) Product Market And Technical Innovation Performance (Pmtip) And Social And Environmementioning
confidence: 99%